2016
DOI: 10.1186/s13045-016-0263-4
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine front-line in 339 patients with myelodysplastic syndromes and acute myeloid leukaemia: comparison of French-American-British and World Health Organization classifications

Abstract: BackgroundThe MDS-IWG and NCCN currently endorse both FAB and WHO classifications of MDS and AML, thus allowing patients with 20–30 % bone marrow blasts (AML20–30, formerly MDS-RAEB-t) to be categorised and treated as either MDS or AML. In addition, an artificial distinction between AML20–30 and AML30+ was made by regulatory agencies by initially restricting approval of azacitidine to AML20–30. Thus, uncertainty prevails regarding the diagnosis, prognosis and optimal treatment timing and strategy for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 74 publications
0
33
0
1
Order By: Relevance
“…On the other hand, in clinical trials, intensive chemotherapy and hypomethylating agents showed 11-13 and 7.7-12.6 months, respectively [13]. Historical approach to treatment focused on chronological age, nevertheless the age cut-offs for using aggressive treatment is likely biased by lesser intent to induce remission and local variability [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in clinical trials, intensive chemotherapy and hypomethylating agents showed 11-13 and 7.7-12.6 months, respectively [13]. Historical approach to treatment focused on chronological age, nevertheless the age cut-offs for using aggressive treatment is likely biased by lesser intent to induce remission and local variability [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutations or aberrant expressions of genes including BCL2, NF-kB and MCL-1 have also been reported and are believed to be responsible for the FLT3 inhibitor resistance. Therefore, combinations of FLT3 inhibitors with other targeted therapies are interesting topics to be explored in the future (106,107).…”
Section: Acquired Resistancementioning
confidence: 99%
“…Таким образом, терапия ГМП может быть эффективной лечебной опцией у пациентов с МДС и ОМЛ с уровнем бластных клеток в костном мозге до 31 % [22]. Этот вывод не подтверждается в другом исследовании [23], в котором пациенты с уровнем бластных клеток 20-30 % имели худшие показатели ОВ, чем пациенты с уровнем бластных клеток менее 20 %. Влияние достижения ответа на ГМП и его сохра-нения до момента выполнения аллоТГСК не опреде-лено.…”
Section: обсуждение и заключениеunclassified